Parabronic esophageal diverticula - Armand Ugon, Alfredo; Mate, Miguel; Carriquiry, Luis (Cirugía del Uruguay, 1975)
Three observations of parabronchial esophageal diverticula are reported. Esophageal dysperistalsís seems to he the most important etiopathogenic factor. The conáition may be. asymptomatic, or may become manifcst through complications, mainly diverticulitis. In other cases they mask sone other associated pathology. They may usually be controlled with a well led medical treatment ( diet, antispasmodic drugs, eventually dilations). Surgery is required in cases- of associated lesions or serious complications ( dysphagia, bleeding, fistulization).